2018
DOI: 10.1002/da.22825
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment gains of a brief exposure-based treatment for PTSD

Abstract: WET is a treatment that is non-inferior to CPT with regard to PTSD symptoms, with treatment effects that are long-lasting. Additionally, both WET and CPT demonstrated substantial effects on depressive symptoms. WET should be considered a good option for PTSD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 24 publications
1
25
0
3
Order By: Relevance
“…Although WET has already been included in the VA/DoD Clinical Practice Guidelines for the Management of PTSD (2017), there is limited data on its efficacy among veterans. To date, one open trial [ 11 ] demonstrated promising efficacy and low treatment dropout (i.e., 14%) and a subsample of 17 veterans included in a randomized controlled trial (RCT) of WET versus CPT found that veterans randomized to WET displayed a significant reduction in PTSD symptoms and only 5% dropped out [ 12 ]. However, these promising findings were preliminary and included a small sample.…”
Section: Introductionmentioning
confidence: 99%
“…Although WET has already been included in the VA/DoD Clinical Practice Guidelines for the Management of PTSD (2017), there is limited data on its efficacy among veterans. To date, one open trial [ 11 ] demonstrated promising efficacy and low treatment dropout (i.e., 14%) and a subsample of 17 veterans included in a randomized controlled trial (RCT) of WET versus CPT found that veterans randomized to WET displayed a significant reduction in PTSD symptoms and only 5% dropped out [ 12 ]. However, these promising findings were preliminary and included a small sample.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 details the study selection process and reasons for study exclusion. Thirteen RCTs and one follow‐up study (Thompson‐Hollands et al., 2018), which provided outcomes related to another included study (Sloan et al., 2018), were included. The characteristics of the included and excluded studies (full‐text screen only) are presented in Supplementary Materials S2.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated reductions in PTSD and related psychopathologies with exposure therapy. 15,16,20,33 However, global functioning is another measure of symptom reduction. Improvements in PTSD with exposure therapy were associated with improvements in psychosocial functioning.…”
Section: Discussionmentioning
confidence: 99%
“…15 The effects of treatment were also long-term, specifically lasting for 60 weeks. 16,17 In order to apply WET to Korean patients, we must consider their different cultural background, which is dissimilar to Westerners. According to a study conducted in Japan, which is culturally similar to Korea, only 15% of respondents choose to disclose their trauma.…”
Section: Introductionmentioning
confidence: 99%